Airway basal stem cells are necessary for the maintenance of functional intraepithelial airway macrophages - Kooistra, Tristan; Saez, Borja; Roche, Marly; Egea-Zorrilla, Alejandro; Li, Dongzhu; Anketell, Dilanjan; Nguyen, Nhan; Villoria, Jorge; Gillis, Jacob; Petri, Eva; Vera, Laura; Blasco-Iturri, Zuriñe; et al. (My University, 2025)
Stem cells are known to provide signals that contribute to the maintenance and function of neighboring cells. We demonstrate that Notch signaling arising from airway basal stem cells is necessary for the function of a unique population of intraepithelial airway macrophages (IAMs) in the murine trachea. Without this stem cell signaling, IAMs lose MHC II expression, which in turn prevents antigen-induced allergic inflammation. Distal murine airways do not harbor basal stem cells, and, in this region of the lung, allergic inflammation proceeds unperturbed. We speculate that the functional coupling of specific anatomically restricted stem cell populations and adjacent immune cells is one mechanism for ensuring that inflammatory responses are compartmentalized to regions of injury. Basal stem cells are found throughout the human airway tree and we demonstrate the existence of human IAM-like cells, suggesting that their interaction may influence airways disease.
Keywords: ddc:610